2008
DOI: 10.1002/jbm.b.31052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of monomer leaching from a dual cured resin cement

Abstract: In the case of resin cement, leaching of TEGDMA was the highest and the cumulative amount of leaching monomers from resin cement was influenced by the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 122 publications
(219 reference statements)
3
32
1
Order By: Relevance
“…Resin-based materials are known to show toxic reactions in cell cultures and various studies have shown that toxicity is primarily induced by monomers released from the material 3,6,12,13,[18][19][20] . In this study, the elution of UDMA and TEGDMA from self-adhesive resin cements in artificial saliva with time is evaluated and biological effects of the cumulative monomer amounts are determined.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Resin-based materials are known to show toxic reactions in cell cultures and various studies have shown that toxicity is primarily induced by monomers released from the material 3,6,12,13,[18][19][20] . In this study, the elution of UDMA and TEGDMA from self-adhesive resin cements in artificial saliva with time is evaluated and biological effects of the cumulative monomer amounts are determined.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a dental resin should have all monomers converted to polymers during the polymerization reaction. Dual-cure materials tend to be more effective in the early stages of polymerization because they contain both photo initiators and components for a chemically activated reaction 19) . Kawahara et al 7) used HPLC to investigate the elution of residual monomers at 1, 3, 6, 12, and 24 h and 3, 7, and 14 days.…”
Section: Monomer Release Analysismentioning
confidence: 99%
See 3 more Smart Citations